Obesity vs. overweight status: differential predictions to poly-substance use in young adulthood - Lanza, H. Isabella; Waller, Kailey; Sevillano, Lalaine (Frontiers in Adolescent Medicine, 2025)
BackgroundThough past research has identified links between higher weight status and substance use in young adulthood, prospective studies are scarce and mixed, the role of higher weight status on vaping is less clear, and little empirical work has examined differences between obesity vs. overweight on poly-substance use. The current study assessed the role of weight status on poly-substance use trajectories across young adulthood.Methods1,303 young adults (20.5 ± 2.3 years; 63% female; 41% Latina/o/x, 30% Asian-American/Asian, 18% Caucasian/White) from a public, urban university were surveyed at six-month intervals from spring 2021 (W1) to spring 2023 (W5). Weight status was measured at W1 with body mass index (BMI) and categorized into obese (BMI ≥ 30.0); overweight (BMI 25.0–29.9); healthy weight (BMI 18.5–24.9); and underweight (BMI < 18.5). Past 30-day use of nicotine vaping, cigarette smoking, cannabis vaping, combustible cannabis, cannabis edibles, and binge drinking across waves were used to identify poly-substance use trajectories with parallel growth mixture modeling (PGMM).ResultsFour trajectories were identified: Nicotine/Tobacco Users and Binge Drinkers (7.2%); Poly-Users (9.8%); Moderate Cannabis Users and Binge Drinkers (18.7%); and Non-Users (64.3%). Obese young adults (vs. healthy weight) had lower odds of belonging to the Nicotine/Tobacco Users and Binge Drinkers trajectory [aOR = .24(.06-.99)] vs. Non-Users trajectory. Overweight young adults (vs. healthy weight) had higher odds of belonging to the Moderate Cannabis Users and Binge Drinkers trajectory [aOR = 1.94(1.25–3.03)] vs. Non-Users trajectory.ConclusionsOverweight young adults' higher odds vs. obese young adults' lower odds of belonging to poly-substance use trajectories suggest overweight young adults may be a key target group for poly-use public health initiatives. Poly-substance use differences between obese and overweight status indicate a greater need for specificity when evaluating relationships between higher weight status and substance use.